Immunohistochemistry-derived subtypes of breast cancer distribution in four regions of Ethiopia - Belachew, Esmael Besufikad; Desta, Adey Feleke; Gebremariam, Tewodros Yalew; Deneke, Dinikisira Bekele; Ashenafi, Senait; Yeshi, Melisachew Mulatu; Fenta, Bizunesh Dires; Alem, Alemwosen T/Hayimanot; Alemu, Addisu; Abafogi, Abdo Kedir; Desta, Tigist; Chanyalew, Menberework; et al. (Frontiers in Endocrinology, 2023)
Different biological characteristics, therapeutic responses, and disease-specific outcomes are associated with different molecular subtypes of breast cancer (BC). Although there have been different studies on BC in the Ethiopian capital city of Addis Ababa, there have been few studies in other parts of the nation, and none have evaluated biological characteristics in other locations in the context of the extensive ethnic and genetic diversity found in Ethiopia. This study was carried out to evaluate the distribution of immunohistochemistry (IHC) subtypes of BCs throughout four Ethiopian regions.Methods: A total of 227 formalin-fixed paraffin-embedded (FFPE) tissue blocks were collected from tertiary hospitals in four Ethiopian regions between 2015 and 2021. The IHC staining was performed for subtyping, ER, PR, HER2, and Ki-67 proliferation markers.The mean age at diagnosis was 43.9 years. The percentage of ER and PR-negative tumors was 48.3% and 53.2%, respectively. The IHC subtypes showed the following distribution: 33.1% triple-negative breast cancer (TNBC), 27.6% luminal B, 25.2% luminal A, and 14.1% HER2 enriched. In multiple logistic regression analysis, grade III and HER2 positivity were associated with larger tumor size, and also originating from Jimma compared to Mekele.Patients with ER-negative, PR-negative, and TNBC were found in 48.3%, 53.2%, and 33.1% of cases, respectively, showing that half the patients could potentially benefit from endocrine treatment. A considerably high prevalence of TNBC was reported in our study, demanding additional research that includes genetic predisposition factors. Additionally, aggressive tumors were found in a high percentage of younger age groups, which must be considered when planning personalized treatment strategies.